Mutação constitucional do controle difuso no Brasil? Uma análise do papel do Senado Federal diante do art. 52, X, da Constituição - Santos, Carlos Victor Nascimento dos (2010)
The goal of this study is to assess the soundness of the thesis that the Brazilian system of diffuse judicial review has undergone a 'constitutional mutation', specifically regarding the Federal Senate’s constitutional prerogative to suspend the enforcement of any law or normative act that has been declared unconstitutional by the Supreme Federal Court by means of concrete review. This 'constitutional mutation' argument has been employed by Justice Gilmar Ferreira Mendes in the judgment of the Reclamação 4335-5/AC by the Brazilian Supreme Federal Court. To assess the consistency of this thesis, this paper (a) investigates the necessary empirical conditions that must be true for such a 'constitutional mutation' argument to be deemed plausible in the Brazilian legal system, and (b) does an empirical analysis of the role of the Brazilian Senate in using the powers conferred to it by article 52, X of the 1988 Constitution. After comparing the data thus obtained with the conditions presented in the conceptual part of the paper, I argue that Justice Mendes’ acknowledgment of the supposed 'constitutional mutation' of article 52, X is ungrounded. This argument also supports the idea that any instances of constitutional reasoning based on 'constitutional mutation' cannot be grounded only on doctrinal and jurisprudential inputs and require empirical analysis in order to be justified.